Introduction to Argentine exceptionalism - Edward L. Glaeser; Rafael Di Tella; Lucas Llach (Latin American Economic Review, 2018)
This article is an introduction to the special collection on Argentine Exceptionalism. First, we discuss why the case of Argentina is generally regarded as exceptional: the country was among the richest in the world at the beginning of the 20th century, but it gradually lost this place of privilege. We discuss that most explanations regarding the hypothesis of Argentine Exceptionalism fall into one or several of four categories. The first explanation is to challenge the exceptionalism hypothesis, either by arguing that the country was not so rich at the beginning of the 20th century or that it is not so poor now. The second explanation states that the country failed to generate growth supporting institutions despite its wealth, thus leading to a relative decline in its income level. The next explanation is that the country faced a series of adverse external shocks which disfavored what had been a successful growth model. Finally, scholars have also stated that exceptionalism is a consequence of poor policy choices, in particular a tendency towards state intervention and isolationism. Next, we introduce the remaining papers of the special collection and how they relate to the aforementioned hypothesis. Finally, we offer some concluding remarks regarding this article.
Keywords: N10; N16; D78; 330; Argentine exceptionalism; Economic history